Reactivity of graphene-supported Co clusters - Waleska-Wellnhofer, Natalie; Arzig, Sophie; Düll, Fabian; Bauer, Udo; Bachmann, Phiona; Steinhauer, Johann; Papp, Christian; Risse, Thomas (Surface Science, 2024)
Graphene-supported Co clusters were investigated by high-resolution XPS, TPD and IRRAS using CO as a probe molecule. CO adsorption was observed at edge, on-top and bridge/hollow sites on the as-prepared clusters. Temperature-programmed XPS showed CO dissociation at T > 300 K. The CO desorption temperatures were determined by TPD measurements to be 260, 320 and 400 K for CObridge/hollow, COedge and COtop, respectively. The CO dissociation products were used to investigate the adsorption of CO on carbon and oxygen precovered Co clusters. Site blocking by these adatoms was found resulting in the absence of COedge (XPS and TPD) and a decrease of the CO adsorption capacity (XPS, TPD and IRRAS). Additionally, no CO dissociation was found on the precovered clusters concluding a blocking of the catalytically active sites which are the edge sites of the clusters.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Cluster chemistry; CO adsorption; Cobalt; Graphene; Supported nanocluster